UCI sports nutrition project: Plate to performance - culinary nutrition support for professional road cycling - Lis, D. M.; Strobel, N. (International Journal of Sport Nutrition and Exercise Metabolism, 2026)
In elite road cycling, nutrition is a critical pillar of performance, with culinary support evolving from a logistical necessity to a core competitive determinant. The collaboration among performance chefs, registered dietitian/nutritionist(s), and soigneurs, collectively termed the Culinary Nutrition Team, is central to translating evidence-based nutrition strategies into practical, palatable food provision. Through an applied lens, this review positions the Culinary Nutrition Team as the operational link through which complex nutrition, physiological, and sport science principles are translated and delivered in day-to-day practice within professional road cycling. The overlapping skill sets of Culinary Nutrition Team members are described, alongside respective roles and responsibilities, in executing nutrition strategies through real-time menu adjustments, management of special dietary needs, and adaptation to environmental and logistical challenges. While common principles underpin effective culinary nutrition support, how those principles are executed in practice is shaped by practitioner training and scope of practice, team structure and maturity, communication pathways, staff dynamics and trust, and the broader cultural and logistical context in which teams operate. In this context, digital tools and technologies (e.g., workload-derived data integration, centralized nutrition management platforms, and biometric wearables) are gaining prominence as innovative approaches to inform energy requirements, support rapid food provision adjustments, and facilitate team-wide communication. However, their effectiveness depends on appropriate validation, integration within established workflows, regulatory approval for in-race, and skilled interpretation. Ultimately, an athlete-centered, systems-based approach to culinary nutrition support embedded within the wider performance team is no longer a marginal gain but a competitive necessity in modern professional road cycling.